2007
DOI: 10.1159/000107710
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Intrarenal 20-Hydroxyeicosatetraenoic and Epoxyeicosatrienoic Acids in the Regulation of Renal Function in Hypertensive Ren-2 Transgenic Rats

Abstract: Background: The present study was performed in hypertensive Ren-2 transgenic rats (TGR) and in normotensive Hannover Sprague-Dawley (HanSD) rats. First, the intrarenal protein expression of CYP4A, the enzyme catalyzing the formation of 20-hydroxyeicosatetraenoic acid (20-HETE), and of CYP2C23, the enzyme responsible for epoxyeicosatrienoic acid (EET) production, was evaluated. Second, the renal functional responses to inhibition of the intrarenal formation of 20-HETE and EETs were investigated. Methods: Renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 91 publications
3
16
0
Order By: Relevance
“…Notwithstanding this conclusion, the important role of CYP-derived eicosanoids in the regulation of renal function and blood pressure as well as in the pathophysiology of hypertension and the associated hypertension-induced end-organ damage has been recently documented for ANG II-dependent forms of hypertension [6-11,16,30-32]. Moreover, disturbed intrarenal production and diminished action of 20-HETE combined with intrarenal deficiency of EETs (a consequence of increased sEH-mediated conversion to biologically inactive DHETEs) have been implicated in the pathophysiology of hypertension in transgenic Ren-2 rats (TGR) [11,13]. Evaluation of the proposed in vivo functional role of 20-HETE and EETs is difficult.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Notwithstanding this conclusion, the important role of CYP-derived eicosanoids in the regulation of renal function and blood pressure as well as in the pathophysiology of hypertension and the associated hypertension-induced end-organ damage has been recently documented for ANG II-dependent forms of hypertension [6-11,16,30-32]. Moreover, disturbed intrarenal production and diminished action of 20-HETE combined with intrarenal deficiency of EETs (a consequence of increased sEH-mediated conversion to biologically inactive DHETEs) have been implicated in the pathophysiology of hypertension in transgenic Ren-2 rats (TGR) [11,13]. Evaluation of the proposed in vivo functional role of 20-HETE and EETs is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that intrarenal 20-HETE exerts also an antihypertensive action is strengthened by the demonstration that chronic blockade of 20-HETE formation promotes the development of salt-sensitive hypertension in otherwise salt-resistant rats [41]. In a clear contrast with the transport inhibitory effect of 20-HETE observed in normotensive rats and in a number of experimental or genetic hypertensive rat models, in a recent study we found that in hypertensive TGR increased intrarenal 20-HETE concentrations cause sodium retention without decreasing renal haemodynamics, which suggests an increase in the tubular sodium transport [13]. Thus, in hypertensive Ren-2 transgenic rats 20-HETE could be pro-hypertensive both owing to its vasoconstrictor and to the sodium retaining activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations